The Dynamics of Legal Protection Implementation for Domestic Violence Victims in Indonesia: Lessons from International Practices - Saragi, Paltiada (Indonesian Journal Publisher, 2025)
This study aims to examine the effectiveness of Indonesia’s legal framework in protecting victims of domestic violence through a normative juridical approach combined with a comparative method. The research analyzes the implementation of Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 12 of 2022 on Sexual Violence Crimes, comparing them with international instruments such as the Domestic Abuse Act 2021 (United Kingdom), the Violence Against Women Act 2022 (United States), and the Istanbul Convention 2011 (Europe). Findings reveal that Indonesia’s legal norms are conceptually comprehensive but remain limited in practice due to structural, cultural, and institutional barriers. Weak coordination among implementing agencies, the insufficient number of Regional Technical Implementation Units for Women and Children Protection (UPTD PPA), and low public awareness continue to hinder effective victim protection. The study recommends harmonizing domestic legislation, strengthening local service institutions, and adopting a victim centered justice approach aligned with international best practices to enhance the protection of women’s rights in Indonesia.